2003
DOI: 10.1515/zna-2003-0102
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Amplification in the Relativistic Restricted Three-body Problem

Abstract: The relativistic equations of motion for the restricted three-body problem are derived in the first post-Newtonian approximation. These equations are integrated numerically for seven different trajectories in the earth-moon orbital system. Four of the trajectories are determined to be chaotic and three are not chaotic. Each post-Newtonian trajectory is compared to its Newtonian counterpart. It is found that the difference between Newtonian and post-Newtonian trajectories for the restricted three-body problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The resulting Lagrangian that describes the planetoid motion in the gravitational field of Earth and Moon reads as [64,65]…”
Section: Quantum Effects On Lagrangian Pointsmentioning
confidence: 99%
“…The resulting Lagrangian that describes the planetoid motion in the gravitational field of Earth and Moon reads as [64,65]…”
Section: Quantum Effects On Lagrangian Pointsmentioning
confidence: 99%
“…Moreover, one should bear in mind that three-body systems display chaotic behavior over sufficiently long times [45]. This implies that there might exist critical combinations of some parameters, and in the neighborhood of such critical values, even a very small perturbation could give rise to orbits that differ a lot from each other.…”
Section: Discussionmentioning
confidence: 99%
“…The problem was later revisited by Douskos and Perdios [2002] and Ahmed et al [2006], who found that the relativistic triangular points are linearly stable in the range of mass rations 0 ≤ µ < µ r , where µ r = µ 0 − 17 √ 69/486c 2 [Douskos and Perdios, 2002], and µ r = 0.03840 [Ahmed et al, 2006]. Among different possible applications of the RR3BP as discussed by Brumberg [1991] and Kopeikin et al [2011], let us also mention the calculation of the advance of Mercury's perihelion made by Mandl and Dvorak [1984], the computation of chaotic and non-chaotic trajectories in the Earth-Moon orbital system by Wanex [2003], the relativistic corrections to the Sun-Jupiter libration points computed by Yamada and Asada [2010a], the analysis of stability of circular orbits in the Schwarzschild-de Sitter space-time performed by Palit et al [2009], and the investigation of the GTR effects in a coplanar, non-resonant planetary systems made by Migaszewski and Goździewski [2009].…”
Section: The Restricted Relativistic Three-body Problemmentioning
confidence: 99%